Study on the correlation between serum IgG4/IgG levels and the development of Graves’ ophthalmopathy - Yuanyuan Deng; Zejin Hao; Shanshan Li; Junping Zhang; Jie Zhang; Huaxia Gan; Wei Cai; Yang Liu; Jixiong Xu (Scientific Reports)
Abstract Graves’ ophthalmopathy (GO) with elevated IgG4 levels has different characteristics from patients with GO who do not have elevated IgG4 levels, but the study findings are contradictory. The goal of this study was first to investigate the relationship between IgG4/IgG and IgG4 levels and the occurrence of GO and then to investigate the clinical and laboratory characteristics of patients with GO who had elevated IgG4 levels. This study control group consisted of 57 Graves’ disease(GD)patients with no complicated ocular disease and a median followup of 54.41 months, while the experimental group included 171 GO patients. The clinical and laboratory characteristics of the GD and GO groups were compared. Using an IgG4/IgG cut-off value of 8%, the GO patients were divided into two groups: high IgG4/IgG and low IgG4/IgG, and the differences in clinical and laboratory characteristics between these two groups, as well as between the GO patients before and after 3 months of treatment, were analyzed. The study results show that serum IgG4/IgG levels were independently correlated with the occurrence of GO, but not significantly correlated with GO activity. Patients with high IgG4/IgG levels of GO exhibit distinct characteristics, which may be associated with an unstable balance of lymphocyte subsets.